Social Public Ministry Project: participation as a strategy for the realization of rights (Emancipação, 2020)
This article addresses the category “social participation” used as a strategy for the materialization of rights, through the Strategic Project “Public Social Ministry” of the State of Paraná. The main objective was toidentify the importance of population participation in the execution of social control mechanisms. We start from the assumption that it is essential the existence, interlocution and good functioning of the participation instances as a fundamental element in guaranteeing the social and political rights of the population. Thus, through the bibliographical review, we constructed an argumentative basis based on some theoretical categories such as: history of the democratic State of rights and the conception of social participationthat enabled us to base the qualitative analyzes of the data collected. Participants were members and servants of the Public Ministry of Paraná and representatives of the Pontifical Catholic University of Paraná, partner institution in the development of actions. Among the many indicators and results obtained, we note the importance of qualified and critical social participation of the population, as a means of guaranteeing social, political and human rights, which result from the recognition of historical achievements arising from struggles and popular organization.
Keywords: Social participation. Rights. Social MP Project.